Does Job Placement Impact Performance? - Srimulatsih, Mahbubah (ADPEBI Publisher, 2023)
Work placement and employee performance is a very important thing to be able to achieve goals in an organization. So we need a proper job placement in accordance with the skills and abilities. This research was carried out at the Office of Population and Civil Registration of Kampar Regency. The purpose of this research is to find out whether there is an effect of work placement on employee performance and to find out how much influence work placement has on employee performance. The research method uses a quantitative approach with questionnaire data collection techniques. The results of the recapitulation of respondents' answers regarding work placement (X) obtained an average value of 3.84 and the results of the recapitulation of respondents' answers regarding employee performance (Y) obtained a value of 3, 97 This shows that the criteria for the respondent's answer are good with the statements that have been submitted. The results of the significant test (t) test, obtained a tcount of 5.620 greater than t table with a ttable value of 2.042, with a significance level of 0.000 <0.05. From the results of the study it can be concluded that work placement has a significant effect on employee performance at the Office of the Population and Civil Registration Office of Kampar Regency